Comparative analysis of chemical composition, antioxidant activity and quantitative characterization of some phenolic compounds in selected herbs and spices in different solvent extraction systems - Sepahpour, Shabnam; Selamat, Jinap; Abdul Manap, Mohd Yazid; Khatib, Alfi; Abdull Razis, Ahmad Faizal (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
This study evaluated the efficacy of various organic solvents (80% acetone, 80% ethanol, 80% methanol) and distilled water for extracting antioxidant phenolic compounds from turmeric, curry leaf, torch ginger and lemon grass extracts. They were analyzed regarding the total phenol and flavonoid contents, antioxidant activity and concentration of some phenolic compounds. Antioxidant activity was determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay and the ferric reducing antioxidant power (FRAP) assay. Quantification of phenolic compounds was carried out using high-performance liquid chromatography (HPLC). All the extracts possessed antioxidant activity, however, the different solvents showed different efficiencies in the extraction of phenolic compounds. Turmeric showed the highest DPPH values (67.83–13.78%) and FRAP (84.9–2.3 mg quercetin/g freeze-dried crude extract), followed by curry leaf, torch ginger and lemon grass. While 80% acetone was shown to be the most efficient solvent for the extraction of total phenolic compounds from turmeric, torch ginger and lemon grass (221.68, 98.10 and 28.19 mg GA/g freeze dried crude extract, respectively), for the recovery of phenolic compounds from curry leaf (92.23 mg GA/g freeze-dried crude extract), 80% ethanol was the most appropriate solvent. Results of HPLC revealed that the amount of phenolic compounds varied depending on the types of solvents used.